2013
DOI: 10.1007/s00464-012-2691-8
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic lung metastasectomies: a 10-year, single-center experience

Abstract: IntroductionThe ideal surgical treatment for pulmonary metastasectomy remains controversial. Minimally invasive surgery may offer advantages for quality of life outcomes, with equivalent oncologic long-term results. The purpose of our study was to confirm the validity of the thoracoscopic approach for pulmonary metastasectomy.MethodsWe retrospectively reviewed 164 patients who underwent 212 lung metastasectomies from January 2000 to December 2010. Complete curative pulmonary resections were performed in 159 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The 3-year overall survival rate and the 3-year intrathoracic disease-free survival rate were 59.8% and 33.4% respectively. Recently, Lo Faso and colleagues [42] reported a single-center series of 164 patients who underwent 212 VATS lung metastasectomy from 2000 to 2011. They performed 133 wedge, 22 segmentectomies, 54 lobectomies and 1 pneumonectomy.…”
Section: Single Center Studies With Vats Metastasectomymentioning
confidence: 98%
“…The 3-year overall survival rate and the 3-year intrathoracic disease-free survival rate were 59.8% and 33.4% respectively. Recently, Lo Faso and colleagues [42] reported a single-center series of 164 patients who underwent 212 VATS lung metastasectomy from 2000 to 2011. They performed 133 wedge, 22 segmentectomies, 54 lobectomies and 1 pneumonectomy.…”
Section: Single Center Studies With Vats Metastasectomymentioning
confidence: 98%
“…This represents selection bias and highlights the careful selection of patients for thoracoscopy. With this in mind, several new studies (albeit with mixed tumor histologies) do support the increasing use of VATS in select patients for pulmonary metastasectomy [34, 35, 36]. The controversy of open vs. VATS resection for PM for sarcoma highlights the importance of careful patient selection and understanding disease behavior.…”
Section: Surgical Technique and Managementmentioning
confidence: 99%
“…Lo Faso et al found nodal involvement in only 20% of patients, and involvement was not significantly associated with an overall difference in survival [34]. In the only study in which a systematic mediastinal and hilar lymph node dissection was performed, Pfannschmidt et al found thoracic lymph node involvement in 20.3% of patients with sarcoma, and an improved median survival for N0 patients (47 months for N0 and 18.3 months for N1, p=0.036) [41].…”
Section: Surgical Technique and Managementmentioning
confidence: 99%
“…We do not recommend performing mediastinal lymphadenectomy. Its impact is negligible (IVD) 85 We recommend, when possible, video thoracoscopy in cases of oligometrical disease or peripheral lesions (IVB) 86 …”
Section: Management Of Local/localized Disease (See Figure 1)mentioning
confidence: 99%
“…Its impact is negligible (IVD). 85 • We recommend, when possible, video thoracoscopy in cases of oligometrical disease or peripheral lesions (IVB). 86 • For patients with synchronous metastases at the diagnosis, in the absence of extrapulmonary disease, the initial treatment of choice is systemic chemotherapy.…”
Section: • Absence Of Metastatic Lesions In Other Locationsmentioning
confidence: 99%